Pengaturan Lampu Lalu Lintas dengan Simulasi Monte Carlo Studi Kasus : Perempatan Daerah Dago Bandung - Iryanto Iryanto; Dinan Andiwijayakusuma (P3M Politeknik Negeri Indramayu, 2016)
One of the areas that often become a source of traffic jam is road intersection. So it will be crucial to manage the intersection. Every intersection in main road is common to have traffic light and every cycle of the lamp, red, green and orange, will influence the traffic. The traffic cycle will have significant role to decrease or increase effects of the problem. Inappropriate regulation for the intersection can cause traffic jam or a heavy traffic jam in the road. Sometimes every intersection needs different rule based on the traffic condition. Therefore is truly needed to manage the traffic light in every intersection. With the simulation we can know whether the rule for the traffic light has appropriated to the intersection's traffic condition. If the rule is not optimal yet, we can change the rule with the optimal one. In the research, two methods are used, using coupling parameter and without coupling parameter. Average of vehicle Arrival in each intersection is used as coupling parameter. As its result, using coupling parameter is better than without using coupling parameter.